Breast Cancer Chemoprevention among High‐risk Women and those with Ductal Carcinoma In Situ. Issue 4 (16th April 2015) - Reimers, Laura L.; Sivasubramanian, Parijatham S.; Hershman, Dawn; Terry, Mary Beth; Greenlee, Heather; Campbell, Julie; Kalinsky, Kevin; Maurer, Matthew; Jayasena, Ramona; Sandoval, Rossy; Alvarez, Maria; Crew, Katherine D.
Abstract Chemoprevention with the anti‐estrogens, tamoxifen, raloxifene, and aromatase inhibitors, reduce breast cancer incidence in high‐risk women; however, uptake has been poor (<5%) in the prevention setting. We assessed use of anti‐estrogens for breast cancer prevention, among high‐risk women seen at an academic breast center, to observe how uptake rates compare in this setting. We collected data on demographics, breast cancer risk factors, and health behaviors via self‐administered questionnaires and medical chart abstraction. Women eligible for chemoprevention with anti‐estrogens had a 5‐year predicted breast cancer risk according to the Gail model of ≥1.67%, history of lobular or ductal carcinoma in situ (LCIS/DCIS), and/or BRCA mutation. We dichotomized anti‐estrogen use as ever or never. Predictors of use were evaluated using multivariable log‐binomial regression. Of 412 high‐risk women enrolled, 316 (77%) were eligible for chemoprevention. Among eligible women, 55% were non‐Hispanic white, 29% Hispanic, 8% non‐Hispanic black, and 7% Asian. Women were grouped based upon their highest category of breast cancer risk (in descending order): BRCA mutation carriers (3%), DCIS (40%), LCIS (22%), and 5‐year Gail risk ≥1.67% (36%). Among those eligible for chemoprevention, 162 (51%) had ever initiated anti‐estrogen therapy (71% tamoxifen, 23% raloxifene, 5% aromatase inhibitor). Anti‐estrogen use was highest among women with DCIS (73%). In multivariable analysis, women with a 5‐year Gail risk ≥1.67% had approximately a 20% lower likelihood of anti‐estrogen use compared to women with DCIS (p = 0.01). In the primary prevention setting, excluding women diagnosed with DCIS, anti‐estrogen use was 37%. Multivariable analysis showed differences in uptake by education and potentially by race/ethnicity. Among high‐risk women seen at a breast center, anti‐estrogen use for chemoprevention was relatively high as compared to the published literature. Clinicians can support high‐risk women by effectively communicating breast cancer risk and enhancing knowledge about the risks and benefits of chemoprevention.